Unravelling the historical biogeography of the European rabbit subspecies in the Iberian Peninsula. (10th November 2022) - Díaz‐Ruiz, Francisco; Vaquerizas, Patricia H.; Márquez, Ana Luz; Delibes‐Mateos, Miguel; Piorno, Vicente; Castro, Francisca; Ramírez, Esther; Farfán, Miguel Ángel; Olivero, Jesús; Real, Raimundo; Villafuerte, Rafael
Abstract: Understanding the biogeography of species in space and time is essential for the development of evidence‐based conservation and management plans. In this paper we propose a biogeographical spatial modelling approach based on the favourability function, and developed under a fuzzy logic framework, to unravel the historical biogeography of the two European wild rabbit subspecies, Oryctolagus cuniculus algirus ( Oca ) and Oryctolagus cuniculus cuniculus ( Occ ), in the Iberian Peninsula (IP). We first reviewed published and unpublished information (PhD theses, scientific papers, technical reports, etc.) on the occurrence of each rabbit subspecies throughout the IP. We compiled data from 201 Iberian rabbit populations and from genetic information of 4348 rabbits that was used to identify subspecies. Only populations in which all rabbits surveyed belonged to one subspecies were considered in the modelling procedure. We modelled rabbit subspecies' distribution separately for populations in which nuclear and mitochondrial DNA sequences were available. We employed a trend surface analysis developed by logistic regressions, which applied the favourability function and fuzzy logic operations. Using our approach we indentify the expansion cores from which both rabbit subspecies would have expanded after isolation during the last glaciations. Furthermore, we reveal the possible existence of a competitive exclusion zone between both rabbit subspecies that may have prevented their further expansion. Finally, our study shows that the Oca subspecies is distributed in north‐western areas previously attributed to Occ . This assessment of the actual and historical distribution of each rabbit subspecies may allow more specific conservation interventions, as the two subspecies are not just genetically distinct but also ecologically and behaviourally different. Our methodological approach could be useful in unravelling the historical biogeography of other lesser‐known species. Abstract : We used biogeographical spatial models to understand the biogeography of the two subspecies of European rabbit that are found in the Iberian Peninsula. After the last glaciation, each subspecies expanded from its own isolated core, as suggested by the two maps. Top: Historical biogeographical distribution of European rabbit subspecies in the Iberian Peninsula obtained by spatial favourability models. Oca: Oryctolagus cuniculus algirus . Occ: Oryctolagus cuniculus cuniculus . BTZ: biogeographical transition zone between historical distributions of both subspecies. HPC: Historical population cores from which subspecies expanded. Bottom: Competitive exclusion areas between rabbit subspecies obtained using the fuzzy intersection between both rabbit subspecies' spatial favourability models. These results propose competitive exclusion as a biological barrier for expansion of both subspecies. RESUMEN EN ESPAÑOL: Entender la biogeografía de las especies en el tiempo y el espacio es fundamental para el desarrollo de planes de gestión y conservación basados en la evidencia científica. En este artículo proponemos una aproximación de modelación biogeográfica espacial basada en la función de favorabilidad, desarrollada bajo un marco teórico de lógica difusa para desentrañar la biogeografía histórica de las dos subespecies de conejo de monte, Oryctolagus cuniculus algirus ( Oca ) y Oryctolagus cuniculus cuniculus ( Occ ), en la Península Ibérica (PI). En primer lugar revisamos información publicada y no publicada (Tesis doctorales, artículos científicos, informes técnicos, etc.) sobre la presencia de cada subespecie en la PI. Recopilamos información para 201 poblaciones ibéricas de conejo de monte y de la información genética de 4348 conejos que fue utilizada para identificar la subespecie. Para el proceso de modelación, solamente se utilizaron aquellas poblaciones en las que todos los individuos analizados pertenecieron a una subespecie. Modelamos la distribución de ambas subespecies por separado para aquellas poblaciones analizadas con ADN mitocondrial y nuclear. Utilizamos análisis de superficies de tendencias mediante regresiones logísticas, aplicando la función de favorabilidad y diferentes operaciones de lógica difusa. Mediante nuestra aproximación identificamos los núcleos de expansión desde los que ambas subespecies podrían haberse expandido después de haber estado aisladas en las últimas glaciaciones. Además, revelamos la posible existencia de una zona de exclusión competitiva entre ambas subespecies que podría haber impedido un mayor rango de expansión. Finalmente, nuestro estudio indica que la subespecie Oca se distribuiría en áreas del noroeste, anteriormente atribuidas a la subespecie Occ . Esta evaluación de la distribución real e histórica de cada subespecie de conejo puede permitir intervenciones de conservación más específicas, ya que las dos subespecies no sólo son genéticamente distintas, sino también ecológica y comportamentalmente diferentes. Nuestro enfoque metodológico podría ser útil para desentrañar la biogeografía histórica de otras especies menos conocidas.